2022
DOI: 10.3390/plants11101348
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Medicinal Mechanisms of Pinellia ternata Breitenbach, a Traditional Medicine for Gastrointestinal Motility Disorders, through Network Pharmacology

Abstract: Pinellia ternata Breitenbach (PTB) is a widely used herbal medicine in China, Japan, and South Korea. It has antiemetic, anti-inflammatory, antitussive, and sedative properties. The raw material is toxic, but can be made safer using alum solution or by boiling it for a long time. In addition, PTB seems to be effective for gastrointestinal motility disorders (GMDs), but this is yet to be conclusively proven. Herein, PTB compounds, targets, and related diseases were investigated using the traditional Chinese med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Research on gastrointestinal motility abnormalities in traditional medicine has been actively conducted [ 31 ]. It was found that the possibility of controlling gastrointestinal movement and reduced gastrointestinal movement increased due to various traditional medicines, such as Pyungwi-san [ 32 ], Lizhong Tang [ 33 ], Poncirus trifoliate fruit [ 34 ], So-Cheong-Ryong-Tang [ 35 ], San-Huang-Xie-Xin-tang [ 36 ], Schisandra chinensis [ 37 ], Ge-Gen-Tang [ 38 ], Liriope Platyphylla Wang Et tang [ 39 ], Hwangryunhaedok-tang [ 40 ], Gamisoyo-San [ 41 ], Banhasasim-Tang [ 42 ], and Pinellia ternata Breitenbach [ 43 ]. In order for the oriental medical approach to become an efficient approach in controlling gastrointestinal motility, large-scale clinical studies are needed to prove the reproducibility and validity of the effects.…”
Section: Discussionmentioning
confidence: 99%
“…Research on gastrointestinal motility abnormalities in traditional medicine has been actively conducted [ 31 ]. It was found that the possibility of controlling gastrointestinal movement and reduced gastrointestinal movement increased due to various traditional medicines, such as Pyungwi-san [ 32 ], Lizhong Tang [ 33 ], Poncirus trifoliate fruit [ 34 ], So-Cheong-Ryong-Tang [ 35 ], San-Huang-Xie-Xin-tang [ 36 ], Schisandra chinensis [ 37 ], Ge-Gen-Tang [ 38 ], Liriope Platyphylla Wang Et tang [ 39 ], Hwangryunhaedok-tang [ 40 ], Gamisoyo-San [ 41 ], Banhasasim-Tang [ 42 ], and Pinellia ternata Breitenbach [ 43 ]. In order for the oriental medical approach to become an efficient approach in controlling gastrointestinal motility, large-scale clinical studies are needed to prove the reproducibility and validity of the effects.…”
Section: Discussionmentioning
confidence: 99%